Synthesis and Crystal Structure of Co(II) Complex with 2,3-Bis(2-pyridyl)-5,8-dimethoxyquinoxaline - LIU, YU-MIN; LIU, HE (Asian Journal of Chemistry, 2010)
A new polypyridyl ligand, 2,3-bis(2-pyridyl)-5,8-dimethoxyquinoxaline and its Co(II) complex have been synthesized and characterized. The crystal structure of Co(II) complex has been elucidated by X-ray diffraction analyses. The ligand acts as a bidentate and the Co(II) center is coordinated to the two nitrogen atoms of the two pyridine group. The formation of infinite quasi one-dimensional chains assisted by the intermolecular face-to-face aryl stacking interactions may have stabilized the crystals of the complex.